Regional strategies as generators of trust between regional actors Case: South Karelia - Ulla Kotonen; Jyrki Ahola (European Regional Science Association (ERSA), 2003)
Our paper is based on some recent studies done in the Department of Business Administration at Lappeenranta University of Technology, the goal of which was to find out whether regional strategy processes help to produce and strengthen the trust between regional actors. The paper is divided into a theoretical and an empirical part. In the theoretical part the focus is to analyze trust, co-operation, partnership, networking and strategy processes (especially a continuous strategy process model) in the context of regional co-operation. Trust and its importance in co-operation, networking and partnership have been studied extensively in the context of the business world, but not so much in the context of regional co-operation. However, trust is one of the most important premises for successful co-operation in the public sector as well. In the empirical part of the paper the focus is to analyze the regional strategy processes - the regional strategies that have been implemented - in late 1990s and after that in the province of South Karelia, Finland. The planning and implementing of these strategies has demanded, and still demands, participation of the central actors in the region. A successful strategy process requires, but also creates cooperation between the different actors. In this cooperation, open communication and interaction, commitment to common goals, and genuine willingness to develop the region are highlighted. Wide strategy projects offer the actors a chance to get to know each other and each others' ways of action thoroughly. This also opens up possibilities for the creation and strengthening of trust between the actors. The paper assesses strategy processes and strategies especially from the point of view of creating and strengthening the trust between regional actors. The main objective in the empirical part is to analyze whether the regional strategy processes have helped to produce and strengthen the trust between the regional actors of South Karelia, and what the level of trust is at the moment. The empirical data was collected with a survey in 2002.
Keywords: 330